The Solar Radiation and Energy Laboratory (ESEL) at Limassol, Cyprus: infrastructure, QA/QC procedures, and first year of results - Charalampous, Georgia; Fragkos, Konstantinos; Fountoulakis, Ilias; Hadjimitsis, Diofantos G.; Kazadzis, Stelios (My University, 2025)
This study presents the infrastructure, measurement procedures and one year of measurements of the newly founded The Solar Radiation and Energy Laboratory (ESEL) at Limassol, Cyprus [34.67°N, 33.04°E, altitude of 31m]. The data include: solar broadband measurements of global horizontal irradiance (GHI), direct normal irradiance (DNI), and diffuse horizontal irradiance (DHI), with an annual availability exceeding 99%, solar spectral measurements at the UV and visible range, infrared measurements and cloud camera information. The measurements underwent rigorous quality control procedures, including range, closure, and consistency tests, ensuring the reliability of the dataset. Annual sums of GHI shortwave (SW) irradiance reveal a total of 2004 kWh/m2 and DNI (SW) of 2307 kWh/m2, emphasizing the region's high solar energy potential. Temporal variations indicate peak solar energy availability during summer, with marked diurnal and seasonal patterns influenced by solar geometry and atmospheric conditions. The station follows the Baseline Surface Radiation Network (BSRN) recommendations for quality control procedures, ensuring robust and reliable data for long-term analysis. Closure tests were performed to verify the consistency among the radiation components by assessing the ratio of diffuse to global horizontal irradiance and the ratio of global horizontal irradiance to the sum of its direct and diffuse irradiance components as they have been measured individually. The latest is expected to remain close to 1, indicating the physical coherence of the measurements. The results confirmed the dataset's accuracy, with some deviations observed under specific atmospheric conditions and due to technical sporadic failures. These measurements represent the first year of operation, but the station is designed for long-term monitoring to support ongoing research and regional energy planning. Having a monitoring station that measures global, diffuse, and direct solar radiation provides highly valuable data across a range of scientific, engineering, and industrial disciplines such as: Renewable Energy (designing and optimizing solar power systems), Meteorology/Climatology (studying climate patterns, energy balance, and atmospheric dynamics), agriculture (applications related with photosynthesis related data), aerosol and atmospheric physics (Studying the effects of particles, gases on solar radiation) and remote sensing (Calibrating/validating satellite data with ground truth measurements).
Keywords: Solar Radiation; Energy Laboratory; Switzerland